Green innovation, green accounting, and performance: The moderating role of green intellectual capital - Sumayyah, Sumayyah; Damayanti, Rizki Wahyuning; Zahara, Inna (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study examines the impact of green innovation and green accounting on financial and environmental performance, with green intellectual capital (GIC) as a moderating variable.Design/Methodology/Approach: The analysis is based on 188 firm-year observations from companies listed on the Indonesia Stock Exchange (2020–2023), selected through purposive sampling. Panel data moderated regression analysis is employed.Research findings: Green process innovation does not significantly affect financial performance but improves environmental performance. Green product innovation negatively impacts financial performance yet positively influences environmental outcomes. Green accounting enhances financial performance but shows no effect on the environment. GIC strengthens the positive effect of green product innovation and green accounting on environmental performance, and also reinforces the link between green product innovation and financial performance. However, GIC does not moderate the effects of green process innovation or green accounting on financial performance.Theoretical Contribution/ Originality: The study offers novel insights into the role of GIC as a strategic intangible asset that enhances the effectiveness of green innovation and accounting practices, thereby bridging a gap in the environmental accounting and sustainability literature, particularly within emerging markets such as Indonesia.Practitioner/Policy implication: Findings underscore the importance of integrating GIC into corporate sustainability strategies and call for stronger collaboration between policymakers and business leaders to support green initiatives without compromising economic performance.Research limitation/Implication: The use of purposive sampling may limit the generalizability of the findings to the broader population of listed firms.